Study of Variation of aerosols on High Mountain, Jomsom - Shrestha, Prakash M.; Joshi, Usha; Chapagain, Narayan P.; Karki, Indra B.; Poudyal, Khem N. (Molung Educational Frontier, 2020)
The daily aerosol optical depth (AOD) data are derived from AERONET over Jomsom (lat.:28.47°N, long.:83.83°E, alt.: 2,700 m above sea level) for a period of one year 2012. Annual mean of parameters of aerosols are calculated. The effect of different physical as well as meteorological parameters on Angstrom exponential (α) were analyzed. Annual mean of Angstrom exponential (α), Angstrom turbidity coefficient (β) and curvature of AOD (a2) are 1.24 ± 0.54, 0.05 ± 0.04, 4.06 ± 1.44 respectively. Annual average of visibility is 18.48 ± 1.093km. Result of this research work is beneficial for the further identification, impact and analysis of aerosols at different places.